The Impact of Domestication on Aboveground and Belowground Trait Responses to Nitrogen Fertilization in Wild and Cultivated Genotypes of Chickpea (Cicer sp.) - Marques, Edward; Krieg, Christopher P.; Dacosta-Calheiros, Emmanuel; Bueno, Erika; Sessa, Emily; Penmetsa, R. Varma; von Wettberg, Eric (Frontiers in Genetics, 2020)
Despite the importance of crop responses to low fertility conditions, few studies have examined the extent which domestication may have limited crop responses to low-fertility environments in above-and belowground traits. Moreover, studies that have addressed this topic have used a limited number of wild accessions, and therefore overlooking the genotypic and phenotypic diversity of wild relatives. To examine how domestication has affected the response of aboveand belowground agronomic traits, we measured root and leaf functional traits in an extensive set of wild and domesticated chickpea accessions grown in low and high nitrogen environments.Unlike previous studies, the wild accessions used in this study broadly capture the genetic and phenotypic diversity of domesticated chickpea's (Cicer arietinum) closest compatible wild relative (C. reticulatum). Our results suggest that domestication of chickpea led to greater capacities for plasticity in morphological and biomass related traits but may have lowered the capacity to modify physiological traits related to water use and gas exchange. Wild chickpea displayed greater phenotypic plasticity for physiological traits including stomatal conductance, canopy level photosynthesis, leaf level photosynthesis, and C/N ratio. In contrast to domesticated chickpea, wild chickpea displayed phenotypes consistent with water loss prevention, by exhibiting lower specific leaf area and stomatal conductance. In addition to these general patterns, our results indicate that domestication dampened the variation in response type to higher nitrogen environments for below-and aboveground traits, which suggests reduced genetic diversity in current crop germplasm collections.